2020
DOI: 10.3389/fpsyg.2020.02123
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Second Language Listening Over the Past Twenty Years: A Review Within the Socio-Cognitive Framework

Abstract: The assessment of second language (L2) listening has received much attention. To understand the state-of-the-art research on L2 listening assessment, a total of 87 studies published in 14 peer-reviewed journals and two research report series between 2001 and 2020 were reviewed, using the socio-cognitive framework for developing and validating listening tests proposed by Weir (2005). Thirteen research themes were identified in relation to the six components of the framework, including test-taker characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 128 publications
(207 reference statements)
0
3
0
Order By: Relevance
“…Calls for changes to listening assessment have occurred for the past two decades with little development in instructional and assessment practices (He & Jiang, 2020). There remains a gap between authentic language and textbook language (Gilmore, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Calls for changes to listening assessment have occurred for the past two decades with little development in instructional and assessment practices (He & Jiang, 2020). There remains a gap between authentic language and textbook language (Gilmore, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A review of 87 listening research studies demonstrated for the past 20 years researchers are still calling for an increase in assessment authenticity emphasizing real-world contexts (He & Jiang, 2020). In the Chinese context, university students have discussed how they were unprepared for their professors' different English-speaking accents and the need to adapt their listening skills (Noman et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…There are also issues with comprehension assessments. For example, though assessments were included in their reporting, the sole use of MCQ in Chen et al (2022) and Aldukhayel (2021) may have led to construct underrepresentation (He & Jiang, 2020). Although Dizon & Thanyawatpokin (2021) assessed both global and detailed understanding using a variety of response methods, these tests were not included in reporting.…”
Section: Research and Pedagogical Implicationsmentioning
confidence: 99%
“…Although progress has been made in identifying specific constructs (e.g., Gu & Yan, 2010), these attempts are inadequate for constructing a satisfactory typology of listening constructs in L2 assessment. Previous reviews, such as those by He and Jiang (2020) and Taylor and Geranpayeh (2011), although extensive, have several limitations. First, they provide narrative accounts of past approaches to testing listening rather than a comprehensive search of L2 listening constructs.…”
Section: Literature Reviewmentioning
confidence: 99%